Hymenaeus abo wiersz godowy Pawła Mankiewicza na tle innych siedemnastowiecznych epitalamiów mieszczańskich - Nowakowski, Michał (Tematy i Konteksty, 2019)
Hymenaeus, or a Mating Poem by Paweł Mankiewicz, found in the second half of the 20th century, is an epithalamion written for the wedding of Barbara Kleinpoldtówna and Jakub Giza in 1642. The author, the newlyweds as well as the commissioners of the piece are all representatives of the bourgeoisie. In many respects, however, Mankiewicz’s poem definitely stands out among other 17th-century bourgeois wedding poems, not imitating epithalamions characteristic of „high” literature, yet introducing valuable historical, moral and epic information.